2021
DOI: 10.1038/s41598-021-83185-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study on asthma and chronic obstructive pulmonary disease overlap reveals aberrant DNA methylations related to clinical phenotypes

Abstract: We hypothesized that epigenetics is a link between smoking/allergen exposures and the development of Asthma and chronic obstructive pulmonary disease (ACO). A total of 75 of 228 COPD patients were identified as ACO, which was independently associated with increased exacerbations. Microarray analysis identified 404 differentially methylated loci (DML) in ACO patients, and 6575 DML in those with rapid lung function decline in a discovery cohort. In the validation cohort, ACO patients had hypermethylated PDE9A (+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…The PTPs remove phosphate groups from tyrosine residues, thereby influencing signal transduction and cellular processes such as cell metabolism, motility and survival. Chen et al ( 24 ) studied epigenome-wide associations between smoke/allergen exposure and the development of asthma and chronic obstructive pulmonary disease, and found that hypomethylated PTPRN2 was associated with rapid lung function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PTPs remove phosphate groups from tyrosine residues, thereby influencing signal transduction and cellular processes such as cell metabolism, motility and survival. Chen et al ( 24 ) studied epigenome-wide associations between smoke/allergen exposure and the development of asthma and chronic obstructive pulmonary disease, and found that hypomethylated PTPRN2 was associated with rapid lung function.…”
Section: Discussionmentioning
confidence: 99%
“…Length of hospital stay (days)22(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) In-hospital mortality2 (3.7) Data are presented as mean ± standard deviation, median (interquartile range), or n (%). PPHN, persistent pulmonary hypertension of the newborn.…”
mentioning
confidence: 99%
“… 52 However, upregulation in EMT-associated proteins could potentially signify a transition of the airway smooth muscle cells into a more contractile phenotype and further support a shift toward airway remodeling. Similarly, increases in pathways involved in myogenesis, 53 cholesterol homeostasis, 54 and STAT5 signaling 55 can also be indicative of a shift toward the asthma phenotype, as all three pathways have been shown to play a role in allergic asthma inflammation and smooth muscle cell contractility. Given the link between many of the highlighted pathways with asthma and the changes in the contractile phenotype of the microtissues, we believe our system provides an important high-throughput avenue for investigation of therapeutics for the repair and reversal of airway smooth muscle hypercontractility and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…4 ). For the majority of genes such as Elac2 , Csnk1a1 , Eif3a , Eif4g2 , Tmed2 and Mpv17l, a role in the pathogenesis of lung diseases was indicated by previous studies 22 27 , although their functions in the neonatal lung remain unexplored. The data resource provided by the study not only gives insight into an unexplored field of significant relevance for studies in lung development but could serve as a guide for reference gene selection, specifically considering commonly relevant biological, technical and experimental conditions.…”
Section: Discussionmentioning
confidence: 99%